2015
DOI: 10.3892/mmr.2015.4635
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of tetrandrine on epidermal growth factor-induced invasion and migration in HT29 human colorectal adenocarcinoma cells

Abstract: Abstract.Tetrandrine has been shown to reduce cancer cell proliferation and to inhibit metastatic effects in multiple cancer models in vitro and in vivo. However, the effects of tetrandrine on the underlying mechanism of HT29 human colorectal adenocarcinoma cell metastasis remain to be fully elucidated. The aim of the present study was focused on tetrandrine-treated HT29 cells following epidermal growth factor (EGF) treatment, and Transwell, gelatin zymography, gene expression and immunoblotting assays were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Human brain Glioblastoma multiforme cancer GBM 8401 cell line was purchased from the Food Industry Research and Development Institute (Hsinchu, Taiwan). Cells were cultured in RPMI‐1640 medium supplemented with 10% FBS, 100 units/mL penicillin and 100 μg/mL streptomycin at 37°C in a 75 cm 2 tissue culture flasks under humidified atmosphere with 5% CO 2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human brain Glioblastoma multiforme cancer GBM 8401 cell line was purchased from the Food Industry Research and Development Institute (Hsinchu, Taiwan). Cells were cultured in RPMI‐1640 medium supplemented with 10% FBS, 100 units/mL penicillin and 100 μg/mL streptomycin at 37°C in a 75 cm 2 tissue culture flasks under humidified atmosphere with 5% CO 2 …”
Section: Methodsmentioning
confidence: 99%
“…Tetrandrine (TET), a bisbenzylisoquinoline alkaloid isolated from the root of Stephania tetrandra S. Moore , has been revealed to induce cell apoptosis in many human cancer cell lines and inhibits migration and invasion in human prostate cancer cells . Furthermore, TET suppresses cancer angiogenesis and metastasis in 4 T1 tumor bearing mice and targets on epidermal growth factor‐induced invasion and migration in HT29 human colorectal adenocarcinoma cells . TET inhibits Wnt/β‐catenin pathway and decreases metastatic tumor antigen 1 (MTA1) expression to modulate hepatocellular carcinoma cell metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine was also found to induce cytotoxicity and apoptosis of human nasopharyngeal carcinoma cells via inducing ROS‐dependent mitochondrial and ER stress pathways and activating Akt/FOXO3 . Inhibition of tumour angiogenesis and metastasis by tetrandrine was gained through modulating ERK and EFGR pathways in human colorectal adenocarcinoma cells . It has been reported that tetrandrine extensive anticancer effects on gastric cancer cells, such as BGC‐823 cells; however, the potential molecular mechanism of tetrandrine on autophagy pathway in gastric cancer cells has not been clearly illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that TET regulates metastatic- and angiogenic-associated proteins, including vascular endothelial growth factor, hypoxia-inducible factor-1, integrin β5, endothelial cell specific molecule-1 and intercellular adhesion molecule-1 ( 28 ). Previously, it was demonstrated that TET targets epidermal growth factor receptor signaling and its downstream molecules contribute to the inhibition of epidermal growth factor (EGF)-induced HT29 cell metastasis in vitro ( 29 ). Furthermore, it was also reported that TET-loaded PVP-b-PCL nanoparticles more efficiently inhibit cell migration and invasion compared with free TET in A549 human lung cancer cells ( 30 ).…”
Section: Introductionmentioning
confidence: 99%